MRI Findings in Neuroferritinopathy - Emiko Ohta; Yoshihisa Takiyama (Neurology Research International)
Neuroferritinopathy is a neurodegenerative disease which demonstrates brain iron accumulation caused by the mutations in the ferritin light chain gene. On brain MRI in neuroferritinopathy, iron deposits are observed as low-intensity areas on T2WI and as signal loss on T2*WI. On T2WI, hyperintense abnormalities reflecting tissue edema and gliosis are also seen. Another characteristic finding is the presence of symmetrical cystic changes in the basal ganglia, which are seen in the advanced stages of this disorder. Atrophy is sometimes noted in the cerebellar and cerebral cortices. The variety in the MRI findings is specific to neuroferritinopathy. Based on observations of an excessive iron content in patients with chronic neurologic disorders, such as Parkinson disease and Alzheimer disease, the presence of excess iron is therefore recognized as a major risk factor for neurodegenerative diseases. The future development of multimodal and advanced MRI techniques is thus expected to play an important role in accurately measuring the brain iron content and thereby further elucidating the neurodegenerative process.